2007
DOI: 10.1080/00016350701586647
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged effect of a mother–child caries preventive program on dental caries in the permanent 1st molars in 9 to 10-year-old children

Abstract: Examination of children 4 years after discontinuation of a caries preventive program reflected a long-term reduction in the DFS score of permanent 1st molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
9
0
7
Order By: Relevance
“…Together, these observations suggest long-term familial behavioural changes. Recently, a similar approach on a broad oral health basis, directed at firsttime mothers during pregnancy, was successful in reducing the caries incidence in the early childhood of their children [Gomez et al, 2007;Plutzer and Spencer, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these observations suggest long-term familial behavioural changes. Recently, a similar approach on a broad oral health basis, directed at firsttime mothers during pregnancy, was successful in reducing the caries incidence in the early childhood of their children [Gomez et al, 2007;Plutzer and Spencer, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of matching genotypes of S. mutants in mother-child pairs, suggesting vertical transmission (5) and the oral health care of pregnant women may cause sustained and long-term improvement of the oral health of children (10,11). However, horizontal transmission has been less studied and results have been contradictory (7,9,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Information is needed on the different sources of infection and colonization by this microorganism in children in order to develop preventive strategies against dental caries (10,11). This paper presents a cross-sectional evaluation of S. mutants genotypes isolated in saliva of 6-7 year-old children in the same class and analyzes possible patterns of horizontal transmission among the children, the genotypic diversity in each schoolchild, and its relationship with caries disease status.…”
Section: Introductionmentioning
confidence: 99%
“…Die Risikoerkennung und -minimierung (Karies, Parodontitis, Mundschleimhauterkrankungen usw.) sowie eine intensive Ernährungsberatung undlenkung der Schwangeren führen bei deren Kindern nachweislich zu einer Verbesserung der Mundgesundheit [2,7,14,15,16,17,18,19,34]. Zudem besteht eine enge Verbindung zwischen Mundgesundheit und allgemeiner Gesundheit.…”
Section: Gesundheitsförderung In Der Schwangerschaftunclassified
“…70% der Studiengruppe waren verglichen mit 33% der Kontrollgruppe kariesfrei. Die ersten Molaren der zweiten Dentition zeigten in der Studiengruppe deutlich weniger Karies [15]. Eine zahnärztliche Mutter-KindBetreuung beginnend in der Schwangerschaft hat somit nicht nur positive Auswirkungen auf die Zähne der ersten, sondern auch auf die der zweiten Dentition.…”
Section: Zusammenfassung · Abstractunclassified